PREVALENCE AND PRESENTATION OF ENDOMETRIOSIS IN PATIENTS ADMITTED IN NISHTAR HOSPITAL, MULTAN - Din, Naseer -ud-; Khan, Attaullah; Illahi, Nudrat (Journal of Ayub Medical College Abbottabad, 2000)
Background: Endometriosis is responsible for varied and disabling symptoms, and its adverse effects on reproductive potential are sources of widespread frustration and disappointment. This study was done to find out the prevalence and pattern of presentation of the patients with endometriosis. Methods: Two hundred and one consecutive patients, aged 20-45 years, having signs and symptoms suggestive of endometriosis, attending the gynaecology outpatient department of Nishtar Hospital, Multan, during one year i.e. 1995 to 1996, were prospectively included in this study. All such patients were subjected to laparoscopy or laparotomy for final diagnosis. The severity of the disease was documented and classified according to the revised American Fertility Society staging system. Results & Conclusions: The prevalence of endometriosis was 5.2% all gynecological admissions. Our findings of a prevalence of endometriosis of 24.88% in 201 laparotomies/laparoscopies, negates the commonly held view that endometriosis is a rare disease in Pakistan. We have also recorded a high incidence of infertility among patients suffering from endometriosis. The prevalence and pattern of presentation of the patients are comparable with the results reported from all over the world. It is, therefore, concluded that endometriosis is as common among Pakistani women as elsewhere in the world. The pattern of presentation and complications are also similar.